Effect of biofertilizer obtained by anaerobic digestion of cassava effluent on the development of crambe plants - Andressa C. Neves; Camila N. Bergamini; Rafaela de O. Leonardo; Manoel P. Gonçalves; Dilcemara C. Zenatti; Eliane Hermes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the effect of applying increasing doses of biofertilizer obtained by the anaerobic digestion of cassava effluent on the development of crambe plants. The experiment was conducted in a protected environment at the Federal University of Paraná (UFPR), Palotina Sector, between April and August 2015. A completely randomized design was used, and five different treatments with the following doses were applied in five replicates: 0, 40, 80, 120, and 160 kg ha-1 of K2O. The following parameters related to plant development were evaluated: final height, stem diameter, number of branches, dry shoot and root biomass, mass of the grains, and oil content. The 160 kg K2O ha-1 dose was found to have the best influence on the plant development, because all the measured parameters reached their highest values at this dose, except for oil content, which attained the highest percentage in the case of the control treatment (0 kg ha-1 of K2O). This study proved that the biofertilizer obtained by anaerobic digestion of cassava effluent can be used as an alternative to regular fertilizers in cultivating crambe.